PENGARUH STANDAR OPERASIONAL PROSEDUR DAN FASILITAS PERUSAHAAN TERHADAP KINERJA KARYAWAN - Dian Puspita Novrianti; Jumaren Jumaren (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2019)
This study aims to find out empirically the effect of operational standard procedures and company facilities on employee performance. The research method used is quantitative research methods. The sampling technique uses a random sampling technique with the number of samples used as many as 136 respondents.The data collection method used is the survey method using a questionnaire which is then processed statistically using the SPSS version 20. The data analysis technique used is multiple linear regression analysis. The results showed that partially the standard operating procedures had a positive and significant effect on employee performance and company facilities had a positive but not significant effect on employee performance. Furthermore, it can be known simultaneously that the operational standards of procedures and company facilities have a positive and significant effect on employee performance